Triple Jump Training Model Development based Circuit Training for Beginners Athletes - Andika, I Gede Angga; Asmawi, Moch (Program Studi Pendidikan Kepelatihan Olahraga Fakultas Ilmu Pendidikan Universitas Bhayangkara Jakarta Raya, 2022)
This study aims to develop a design for the triple jump to obtain empirical data about the effectiveness of the triple jump-based circuit training model for beginner athletes. The research method used in this study is the research and development method of Borg and Gall which consists of ten steps. The subjects of this study were male and female athletes in Klungkung regency specifically for triple jump numbers. This research resulted in 10 final training models that have gone through expert evaluations, trials, and revisions. In testing the effectiveness of the training model by using